Drug Repurposing Strategy (DRS): Emerging Approach to Identify Potential Therapeutics for Treatment of Novel Coronavirus Infection - Sahoo, Biswa Mohan; Ravi Kumar, B. V. V.; Sruti, J.; Mahapatra, Manoj Kumar; Banik, Bimal K.; Borah, Preetismita (Frontiers in Molecular Biosciences, 2021)
Drug repurposing is also known as drug repositioning or therapeutic switching. It is a process of identifying the new therapeutic agents from the existing FDA approved clinically used drugs. It is an effective strategy for developing drug candidates with new pharmacological or therapeutic properties. As the drug discovery is a costly, time-consuming, laborious, and highly risk process, the novel approach of drug repositioning is employed to increases the success rate of drug development. This strategy is more advantageous over traditional drug discovery process in terms of reducing duration of drug development, low-cost, highly efficient and minimum risk of failure. In addition to this, Coronavirus disease (COVID-19) was declared as global pandemic by World health organization on 11th February 2020. Currently, there is an urgent need to develop suitable therapeutic agents for the prevention of the outbreak of COVID-19. So, various investigations were carried out to design novel drug molecules by employing drug repurposing approach to identify anti-COVID-19 drugs, which can act as promising inhibitors against coronavirus proteins. It has been reported that Covid-19 can infect human respiratory system by entering into the alveoli of lung via respiratory tract. So, the infection occurs due to specific interaction or binding of spike protein with angiotensin converting enzyme-2 (ACE-2) receptor. Hence, drug repurposing strategy is utilized to identify suitable drugs by virtual screening of drug libraries. This approach helps to determine the binding interaction of drug candidates with target protein of coronavirus by using computational tools such as molecular similarity and homology modeling etc. Molecular docking and binding free energy calculations are also performed to predict the drug-receptor interactions and binding affinity. The methodologies involved in drug repurposing can be categorized into three groups such as drug-oriented, target-oriented and disease or therapy-oriented depending on the information available related to quality and quantity of the physico-chemical, biological, pharmacological and toxicological property of drug molecules. This review focus on drug repurposing strategy applied for existing drugs including Remdesivir, Ribavirin, Baraticinib, Tocilizumab, Chloroquine, Hydroxychloroquine, Prulifloxacin, Carfilzomib, Bictegravir, Nelfinavir,Tegobuvir and Glucocorticoids etc to determine their effectiveness towards COVID-19.